A novel Screening Methods using SSCP –PCR to Detect Variations Among three Varieties of Trigonella Foenum Graecum L. Collected from Different Regions in Iraq - Zahraa Abid Nima Al-Yasiry; Jawad K. Abood Al-Janabi; Basheer Al-Alwani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Fenugreek is one of the most commonly used herbal medicinal plants. Another benefit of fenugreek seedsis that it is used to enhance the flavor, color and texture of fruit. Fenugrek comprises a number of chemicalcomponents such as trigonellines, choline, flavonoids and fixed oils. SSCP –PCR is useful to reach rare andendemic species’ genetic diversity and also to resolve genetic links between populations. . PCR amplificationof DNA. Genotyping of ITS4 was performed using a polymerase chain reaction technique, followed by singlestrandconformation polymorphism. Accordingly, these DNA polymorphisms were confirmed using DNAsequencing. The results appeared that the presence of three different haplotype patterns named accordingto the number of bands were 4-bands, 3-bands, 2 –bands using SSCP –PCR technique. The pattern of allresolved SSCP bands can however be difficult to establish using gel visualisation alone. This polymorphismsof DNA must then be verified by the use of DNA sequencing. The findings of the sequence shown that thehaplotypes of the ITS region have been identified by several SNPs.Conclusion: our findings indicated that SSCP-PCR technique is more informative for evaluation of geneticdiversity and relationships among fenugreek populations.